2019
DOI: 10.21577/0103-5053.20190046
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Antibiotics Residues in Milk Using a QuEChERS Method Using Full Factorial Design and Liquid Chromatography-Tandem Mass Spectrometry

Abstract: This study evaluated different methods of extraction based on quick, easy, cheap, effective, rugged and safe (QuEChERS) method for analysis of the antibiotics ceftiofur, cloxacillin and enrofloxacin in milk using ultra-performance liquid chromatography-tandem mass spectrometry. The QuEChERS acetate method has been shown to be inefficient for extracting such antibiotics. The optimized QuEChERS method presented excellent recoveries, from 95 to 99%. A complete factorial design was used to evaluate the effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…The screening tests are nonspecific, while the chromatographs are specific and quantify the substance; however, they are laborious, use many chemical reagents, require trained personnel and their analytical speed is low 2,36 . Even with studies to increase their analytical efficiency, 37–39 chromatographic techniques continue to use noxious reagents, requiring time and trained personnel. For the offer of safe food, it is essential that the number of samples evaluated increases, which implies the search for other techniques and methodologies.…”
Section: Resultsmentioning
confidence: 99%
“…The screening tests are nonspecific, while the chromatographs are specific and quantify the substance; however, they are laborious, use many chemical reagents, require trained personnel and their analytical speed is low 2,36 . Even with studies to increase their analytical efficiency, 37–39 chromatographic techniques continue to use noxious reagents, requiring time and trained personnel. For the offer of safe food, it is essential that the number of samples evaluated increases, which implies the search for other techniques and methodologies.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, pharmaceuticals for human use can also be detected in food matrices as a result of their spread in environmental matrices mainly due to the disposal of biosolids in soils, the irrigation of recycled water, or from surface waters receiving wastewater treatment plant effluents. The detection of pharmaceutical drug residues in milk has been reported in previous studies [4][5][6][7][8]. Therefore, the study of pharmaceutical drug residues in food commodities, as well as the monitoring of compliance with MRLs, requires sensitive and rapid analytical methods capable of determining trace levels of a large number of pharmaceuticals in milk in a single analytical procedure.…”
Section: Introductionmentioning
confidence: 98%
“…QuEChERS is a quick, easy, cheap, effective, robust, and safe extraction compared to the above methods, which may present some difficulties related to time consumption and labor intensity, the low recovery of some target compounds, poor reproducibility, and method improvement [20]. Various modifications of QuEChERS extraction have been reported in the literature for the analysis of pharmaceutical drug residues in milk, using different sorbents for the clean-up step or a combination of them, e.g., octadecylsilane, (C18) as the usual sorbent to improve extraction on high-fat food matrices, primary secondary amine (PSA), and sodium acetate (NaOAc) [6,16,21,22]. Moreover, the Enhanced Matrix Removal-Lipid (EMR-Lipid) is a new product used as a dispersive SPE (dSPE), promising the highly selective removal of lipids, without the retention of the analyte.…”
Section: Introductionmentioning
confidence: 99%
“…The modified QuEChERS has shown that it is very efficient for detecting enrofloxacin residues in the milk and cheese. It has been used in many studies, the most recent of which is a study published by Grabsk et al (2019), and aimed at determining several antibiotics residues, including enrofloxacin in milk and dairy, through the modified QuEChERS method, Full Factorial Design and Liquid Chromatography-Tandem Mass Spectrometry (Grabsk et al, 2019).…”
Section: Extraction Methods Of Enrofloxacin From Milk and Chesses-dem...mentioning
confidence: 99%
“…After that, the extraction salts, QuEChERS salt, were added to the tube then shacked again by hand for 10 minutes, then centrifuged for 5 min at 5000 rpm at 4 o C. After the centrifuge was done, 5 ml of the upper layer of the polypropylene centrifuged tube were removed using a pipette and added to a dispersive EMR tube previously activated with 5 ml water, after which the latter tube undergone shaking by hand for 3 mins, followed by centrifugation for 5 min at 5000 rpm at 4 o C. Once the centrifugation was performed, 5 ml were removed from the upper layer of the polypropylene centrifuged tube and added to the polish tube, and got mixed by shaking for 1min, and then put in the polypropylene centrifuge again for 5 min at 14000 rpm at 4 o C. Lastly, the resultant liquid was filtered with pvdf of pore size 0.22 micron, to remove any residual lumps. This step is considered as a cleaning step for the extraction (Grabsk et al, 2019). After extracting the enrofloxacin residues from the cheese or milk samples, the vial containing the residues was placed in the Liquid Chromatography-Mass Spectrometry LC-MS (SCHIMADZU LCMS-8045)…”
Section: Extraction Methods Of Enrofloxacin From Milk and Chesses-dem...mentioning
confidence: 99%